Is Trust Necessary to Increase Loyalty in Adult Consumers? - Kinanti Alvani Pane; Martina Dwi Mustika; Bertina Sjabadhyni (PSIKODIMENSIA, 2018)
The aim of this study is to examine if brand experience can predict brand loyalty of older adult consumers through brand trust. This cross-sectional study involved 390 Indonesian older adult consumers of a mineral water who completed a self-report questionnaire. Mediation analysis suggested that brand experience was significant for predicting brand loyalty, either directly or indirectly, suggesting partial mediation. This result further implied that older adult consumers’ experience of a brand can maintain ongoing brand loyalty.In addition, brand trust does not necessarily influence the relationship between brand experience and brand loyalty, which implies that experience is sufficient to maintain older adult consumers’ loyalty to the product. The limitations of this research and potential future research is also discussed